Gastronomi dalam Cerita Rakyat Ainu Jepang - Ida Ayu Laksmita Sari; I Nyoman Darma Putra; Ni Luh Kade Yuliani Giri (LP2M ISBI Bandung, 2020)
ABSTRACTThis article analyzes the gastronomic aspects of the Ainu folklore in Japan. Gastronomic aspects examinedinclude how Ainu folklore narrates how they collect and cook food materials, how they consume, andwhat cultural values are attached to both the process of food production and consumption. The studyapplied library research and the object of analysis were selectively chosen from Ainu Mukashi Banashi’sbook: Hitotsubu no Satchiporo (2012), an anthology of Ainu folklore edited by Kayano Shigeru. Thestories chosen analyzed by the literary anthropology theory. The results show that the Ainu folklorecontains narratives about how people collect food, cook, and consume them. The study of the gastronomicnarratives of Ainu folklore presents a novelty that folklore not only contains a moral message for characterformation but is also a medium for preserving and continuing food and culinary culture across time andgenerations.Keywords: Ainu folktale, literary gastronomy, traditional food of Ainu JapanABSTRAKArtikel ini menganalisis aspek gastronomi dari cerita rakyat Ainu Jepang. Aspek gastronomiyang dikaji meliputi bagaimana cerita rakyat Ainu menceritakan cara mereka mengumpulkandan memasak bahan makanan, bagaimana mereka mengonsumsi, dan nilai-nilai budaya apayang melekat pada proses produksi dan konsumsi makanan. Penelitian dilakukan dengan risetperpustakaan dan objek kajian dipilih secara selektif dari buku Ainu Mukashi Banashi: Hitotsubuno Satchiporo (2012), sebuah antologi cerita rakyat Ainu dengan editor Kayano Shigeru. Datadianalisis dengan teori antropologi sastra. Hasil penelitian menunjukkan bahwa cerita rakyatAinu mengandung narasi tentang cara masyarakat mengumpulkan bahan makanan, memasak,dan mengkonsumsinya. Studi tentang narasi gastronomi cerita rakyat Ainu menyajikan halbaru bahwa cerita rakyat tidak saja mengandung pesan moral untuk pembentukan karaktertetapi juga menjadi media untuk melestarikan dan meneruskan budaya makanan dan kulinerlintas waktu dan generasi.Kata Kunci: cerita rakyat Ainu, gastronomi sastra, makanan tradisional Ainu Jepang